Article Review : Potensi Antioksidan Ekstrak Batang Bambu Kuning (Bambusa Sp) Sebagai Pencegahan Penyakit Asma - Ardilah Ardilah; Ishmah Ulya; Sri Wahyuni; Anggi Aulia Nur Fazri; Mhd. Zaky Daniyal; Panji Ramadhani Panjaitan; Adhika Dwiputri Ilafi; Nurul Adila Damanik (Journal Syifa Sciences and Clinical Research, 2023)
Asthma one of the most common non-communicable diseases in the world characterized by varied as well as recurrent symptoms, airflow obstruction, bronchial hyperresponsiveness, and inflammation. Asthma the most common chronic disease (4,6%), followed by golden and mood disorders (4,1%), attention deficit hyperactivity disorder (3,6%), abdominal pain (2,8%), presence (2,8%), learning disorders (2%), congenital skeletal deformities (1,6%), migraine (1,4%), morbid obesity (1,4%), and autism spectrum disorders (1,1%). Worldwide, it is estimated that around 300 million people are affected by asthma, and by 2025 the number of affected patients is growing exponentially with the addition of 100 million people affected by the condition. With the increase in asthma makes motivation and desire high to seek and find effective first-aid solutions for asthma prevention. So this solution aims to provide first aid in the prevention of asthma. In this article, the idea is given in the form of antioxidant benefits of yellow bamboo stem extract (Bambusa sp) as first aid for the prevention of asthma. Yellow bamboo stems contain antioxidants that are useful for preventing asthma. So it is hoped that this idea will have a good impact on people with asthma and be able to provide first aid for the prevention of asthma.